Model Hipotesis Kriteria Desain Pendekatan Feminisme untuk Perempuan Korban Kekerasan - Nada Haifa Adilah; Hanson Endra Kusuma; Rr Diah Asih Purwaningrum (RUAS)
Cases of violence against women, especially in the domestic sector or home, have been increasing every year in Indonesia. This research aims to develop a hypothesis model of design criteria with a feminist approach for women victims of violence. Data collection method was conducted by reviewing relevant archival sources, and data analysis method was carried out using the summative content analysis method. The results show a model hypothesis of the design criteria combining three approaches: feminism, therapeutic architecture, and crime prevention through environmental design (CPTED), totaling 29 design criteria. This research fills the knowledge gap by providing focused design criteria addressing the needs of women victims of violence, which can be used as a basis for designing. The practical implications include improved design strategies that promote a healing environment, empowerment, and safe of security for women victims of violence.